Гибридные газотурбинные установки на топливах биологического происхождения - Яновский, Л. С.; Байков, А. В.; Чухарев, В. Ф.; Кулаев, В. В.; Цодиков, М. В. (Eastern-European Journal of Enterprise Technologies, 2009)
The opportunity of creation of a new kind газотурбинных power installations in which the traditional chamber of combustion is replaced by the battery solide-oxide fuel elements is considered. It is shown, that modern technologies ТОТЭ allow to increase considerably specific capacity, efficiency and a resource of power installation. There is real a generation of the electric power with specific volumetric capacity at a level of 1 МВт/м, at a resource of fuel elements reaching till 80000 hours.